The impact of ICT investments on the relative demand for high-medium-, and low-skilled workers: Industry versus country analysis - Dorothee Schneider (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
In this paper I analyze the effects of information and communication technology (ICT) on compensation shares of high-, medium-, and low-skilled workers. Com- pared to other studies, I investigate this question using a considerably richer data set with respect to the length of time series, set of countries and industries, and information on ICT. Next to investigating the influence of ICT in 14 countries, I concentrate on the analysis in 23 separate industries. The results I find show that the skill-biased technological change hypothesis is rejected if single countries are analyzed with an industry panel, while I find that technological change is a cause of changes in the relative compensation shares in single industries. Here there is a positive influence of ICT on high-skilled workers' relative compensation for the time before 1995, while ICT investments drive the medium- and low-skilled com- pensation shares together for a substantial amount of industries, especially since 1995.
Keywords: J21; J23; J31; 330; ICT; Skill; Income Inequality; Labor Demand; Informationstechnik; Investition; Technischer Fortschritt; Arbeitsnachfrage; Qualifikation; Lohnstruktur; Einkommensverteilung; Schätzung; Welt